Escherichia coli O157 in fish: Prevalence, antimicrobial resistance, biofilm formation capacity, and molecular characterization. (November 2020) - Onmaz, Nurhan Ertas; Yildirim, Yeliz; Karadal, Fulden; Hizlisoy, Harun; Al, Serhat; Gungor, Candan; Disli, H. Burak; Barel, Mukaddes; Dishan, Adalet; Akai Tegin, Ruslan Adil; Simsek, Emrah
Abstract: This study was performed to survey the incidence of Escherichia coli O157:H7 contamination in fish samples which were obtained from different fish farms and retail markets. For this purpose, a total of 140 fish samples were analyzed according to ISO 16654 and screened for virulence genes by mPCR. Antibiotic susceptibility tests were performed with the disc diffusion method and isolates were genotyped by using Enterobacterial repetitive intergenic consensus (ERIC) PCR. Of the 140 analyzed sample, two (1.4%), from the same farm, were found to be contaminated with E. coli O157 serogroup, one of which harbored stx1 and the other eaeA gene. E. coli O157 serogroup were resistant to only ciprofloxacin and were not capable of forming biofilm and their ERIC-PCR patterns were different. In conclusion, the existence of pathogenic E. coli O157 serogroup in fish samples might be a significant threat to public health and fish could serve as a vehicle for transmission of these bacteria to consumers in Turkey. Highlights: The prevalence of E. coli 0157:H7 in fish farms The ERIC-PCR and virulence profiles of each of the isolated E. coli O157 serotypes were different The existence of pathogenic E. coli O157 serotypes in fish samples might constitute a significant threat for public health